Towards a new anthropology of the embodied mind: Maine de Biran's physio-spiritualism from 1800 to the 21st century - Milz, Manfred (Studies in mysticism, idealism, and phenomenology, 2023)
"This exploration in the history of ideas examines the groundbreaking notion of the embodied mind: consciousness is generated through frequent interaction between the voluntary and the spiritual. The conscious, active self is constituted in its sovereign autonomy, as free and undivided, by an inner act of willful resistance, a physical effort towards its own body and the world. For the first time, a multidisciplinary group of senior and junior researchers from Japan, USA and Europe investigate origins and discursive cross-fertilization of this concept around 1800, an intermediary stage between 1870 and 1945, and its influence upon existentialism, phenomenology, and deconstructivism during the postwar-period and beyond, from 1943 to 2010"--